Genome-Wide SNP Data Revealed Notable Spatial Genetic Structure in the Deep-Sea Precious Coral Corallium japonicum - Takata, Kenji; Iwase, Fumihito; Iguchi, Akira; Yuasa, Hideaki; Taninaka, Hiroki; Iwasaki, Nozomu; Uda, Kouji; Suzuki, Tomohiko; Nonaka, Masanori; Kikuchi, Taisei; Yasuda, Nina (Frontiers in Marine Science, 2021)
Estimating the spatial extent of gamete and larval dispersal of deep-sea coral species, is challenging yet important for their conservation. Spatial autocorrelation analysis is useful for estimating the spatial range of dispersal of corals; however, it has not been performed for deep-sea coral species using genome-wide single nucleotide polymorphisms (SNPs). In this study, we examined spatial genetic structure of a deep-sea coral species—Japanese red coral, Corallium japonicum, which suffers from over-harvesting because of its high commercial value. We also examined the power of detecting significant spatial genetic structure by changing the number of loci and the proportion of missing data using both de novo analysis and mapping analysis. Similar results were obtained for both de novo and mapping analysis, although a higher number of loci were obtained by the mapping method. In addition, “many SNPs with a lot of missing data” was generally more useful than “a small number of SNPs with a small amount of missing data” to detect significant fine-scale spatial genetic structure. Our data suggested that more than 650 neutral SNPs were needed to detect significant fine-scale spatial genetic structure. All correlograms showed the spatial dispersal range within Kochi for the C. japonicum population was less than 13 km, suggesting that over-harvesting of C. japonicum within a diameter of approximately 13 km in the Kochi area should be avoided, as it can cause local extinction of the species.